Bringing suspected terrorists to justice? Revealing bias against Muslims in applied counter terrorism by the U.S - Carter, Brittnee (Contemporary justice review, 2020)
This study analyzes the conditions under which the U.S. engages in active counterterrorism approaches. Specifically, it examines the active criminal justice approach which views terrorism as a crime and the military approach which views terrorism as an act of wars and seeks to uncover under what conditions the U.S. will employ one approach over the other. Using evidence from the U.S. from 1970–2014, content analysis is performed to reveal the conditions that elicit criminal justice or military responses to terrorism. The findings suggest biases across the two measures where a criminal justice approach is employed mainly against perpetrators from Western nations and U.S. allies, while a military approach is disproportionately used against Muslims, especially those affiliated with al-Qaeda, Taliban, and al Shabab. The results also suggest, contrary to theoretical conceptualizations, that counterterrorism measures within a criminal justice approach are no less likely than those of a military approach to commit human rights violations.